Learning Outcomes in Sustainability Education Among Future Elementary School Teachers. (March 2017) - Foley, Rider W.; Archambault, Leanna M.; Hale, Annie E.; Dong, Hsiang-Kai
Universities and colleges around the world are exploring ways of reorganizing curricula to educate future leaders in sustainability. Preservice teachers hold tremendous potential to introduce concepts of sustainability far earlier than post-secondary education. However, there is little research of such efforts to yield changes in future elementary school classrooms. This article shares a new, required course—Sustainability Science for Teachers (SSFT)—that is designed to present sustainability topics to preservice teachers. Using the course as a case, we ask: Do preservice teachers acquire skills and content knowledge in sustainability, and does that experience translate to elementary classrooms? Pre- and post-test data from 234 students and a follow-up survey with 103 respondents offers evidence towards addressing this question. Analysis shows preservice teachers gain skills in systems thinking and develop content knowledge in sustainability. This study suggests sustainability is being introduced into elementary classrooms after preservice teachers were required to take a course in sustainability.